2011
DOI: 10.1152/physiol.00037.2010
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D Signaling: Multiple Biological Functions in Health and Disease

Abstract: Protein kinase D (PKD) is an evolutionarily conserved protein kinase family with structural, enzymological, and regulatory properties different from the PKC family members. Signaling through PKD is induced by a remarkable number of stimuli, including G protein-coupled receptor agonists and polypeptide growth factors. PKD1, the most studied member of the family, is increasingly implicated in the regulation of a complex array of fundamental biological processes, including signal transduction, cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
228
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(241 citation statements)
references
References 117 publications
6
228
1
2
Order By: Relevance
“…We tested whether cortactin was a direct substrate for aPKCζ/ι by incubating purified GST-tagged human cortactin in the presence of recombinant human aPKCι. Phosphorylation was detected with antibodies raised against cortactin phosphoSer298, which was recently identified as a phosphorylation site for aPKCζ/ι-related PKD (35,36). In higher metazoans, mRNA splicing generates cortactin variants with four, five, or six conserved tandem actin-binding repeats in which repeats 5 and 6 are the most conserved (37).…”
Section: Apkcζ/ι-dependent Phosphorylation Of Cortactin Controls Itsmentioning
confidence: 99%
“…We tested whether cortactin was a direct substrate for aPKCζ/ι by incubating purified GST-tagged human cortactin in the presence of recombinant human aPKCι. Phosphorylation was detected with antibodies raised against cortactin phosphoSer298, which was recently identified as a phosphorylation site for aPKCζ/ι-related PKD (35,36). In higher metazoans, mRNA splicing generates cortactin variants with four, five, or six conserved tandem actin-binding repeats in which repeats 5 and 6 are the most conserved (37).…”
Section: Apkcζ/ι-dependent Phosphorylation Of Cortactin Controls Itsmentioning
confidence: 99%
“…PKDs are mainly activated by PKC (23,24). PKDs regulate many cellular functions, such as gene expression, cell adhesion and migration, and protein transport at the trans-Golgi network, etc.…”
mentioning
confidence: 99%
“…PKDs regulate many cellular functions, such as gene expression, cell adhesion and migration, and protein transport at the trans-Golgi network, etc. (23,24). PKD1 is an important sensor of oxidative stress (25,26), which is activated by ROS-PKCδ and subsequently induces NF-κB activity.…”
mentioning
confidence: 99%
“…In most cases, PKD1 phosphorylates a sequence characterized by L/V/I at position -5 and R/K at position-3 PKD1, dopamine D1 receptor, and cocaine addiction N Wang et al (Rozengurt, 2011). The S421 identified in the present study does not fit the classical consensus phosphorylation sites for PKD1 (Supplementary Figure 1c).…”
Section: Discussionmentioning
confidence: 54%
“…To date, PKD1 is the best-characterized isoform of this family (Rozengurt et al, 2005;Steinberg, 2012). PKD1 has a vital role in various important biological processes, including cell proliferation and differentiation, vesicle trafficking and secretion, immune regulation and cardiac hypertrophy, and contraction (Rozengurt, 2011). In the nervous system, we first found that PKD1 has an important role in inflammatory heat hyperalgesia through an interaction with transient receptor potential vanilloid 1 (Wang et al, 2004;Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 97%